Effect of sowing date on the incidence of loose smut, flag smut and seed gall of wheat (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted to find out the effect of delay sowing on incidence of loose smut (Ustilago tritici), flag smut (Urocystis agropyri) and seed gall (Anguina tritici) of wheat. Varieties WH 896 and Raj 1555 were free from loose smut at all dates of sowing. At normal date of snwing (25 November) disease incidence varied from 28.18% (HD 2285) to 43.18 % (Sonalika). Due to delay in sowing by 20 days (15 December), the disease incidence was reduced to 21.33-38.18% and delay by 35 days (30 December) it was reduced to 18.62% -32.5 % on all susceptible varieties. At all dates of sowing, varieties WH 283, WI-I 291, WH 896 and Raj 1555 were not infected with flag smut. Other varieties were infected with the disease showing 1.3-14.57, 1.11-11.83 and 0.83-9.14% incidence at the sowing dates of 25 November (normal), 15 December (delay) and 30 December (delay), respectively. All of the varieties tested in this study were infected with seed gall nematode and disease incidence increased with delay in date of sowing. The ranges of the disease incidence were 8.16-20.14, 12.33-28.91 and 14.16-36.66% at first, second tnd third date of sowing, respectively.Key Words: Loose smut; flag smut; seed gall nematode; wheat; sowing date.DOI: 10.3329/bjar.v34i1.5746Bangladesh J. Agril. Res. 34(1) : 1-4, March 2009